Leaf Flavonoids of Chrozophora Neck (Euphorbiceae) Members in Markazi Province Using Chromatographical Methods - M Noori; H Zare Mayvan; A Mazaheri (Institue of Medicinal Plants, ACECR, 2012)
Background: Flavonoids are as one set of the polyphenolic compounds among secondary metabolites in different organs of plants that are used in plant chemotaxonomy and pharmacognosy. They have basic role in pollination and life cycle of anthmophyllus plants and also their spreading abroad and survival.   Objective: The aim of this study was to compare the leaf flavonoids profiles of Chrozophora Neck populations in Markazi Province, Iran.   Methods: Phytochemical studies on 25 collected Chrozophora populations of 2 species ( C. hierosolymitana and C. tinctoria : Euphorbiaceae family) from different parts of Markazi Province area were done using 2-dimentional paper chromatography (2-DPC) and thin layer chromatography (TLC). Voucher specimens of each population were prepared for reference as herbarium vouchers.   Results: Results showed all of populations contain flavonoid sulphates, flavone C and C-/O-glycosides and aglycon. Also all of studied populations have apigenin and quercetin while rutin was just found in 4 populations of C. tinctoria species that is recorded first time for Markazi Province. Conclusion: All of studied populations have flavonoid compounds that have variation in their flavonoid type and number.